AB0298 Relationship between foot deformity and disease stage in patients with rheumatoid arthritis. (23rd January 2014) - Mamoto, K.; Koike, T.; Okano, T.; Tada, M.; Sugioka, Y.; Wakitani, S.; Nakamura, H.
Abstract : Background: Foot deformities frequently arise in patients with rheumatoid arthritis (RA). Conditions such as hallux valgus or flat feet might cause gait dysfunction and lead to disability. However, the progression of foot deformity is unclear. Objectives: To identify, determine relationships with disease stage and clarify the progression of foot deformities to provide more appropriate therapies for patients with RA. Methods: The prospective cohort TOMORROW (TO tal Management O f R isk factors in R heumatoid arthritis patients to lOW er morbidity and mortality; clinical trial registration number, UMIN000003876) study was started during 2010. We examined anteroposterior and lateral radiographs obtained from 416 weight-bearing feet of 208 patients with RA from this cohort. The mean age and mean disease duration were 58.2 and 14.4 years, respectively. We finally analyzed 196 patients 387 feet excluding those that had been surgically treated. We classified articular destruction from the radiographs based on Steinbrocker's classification. We measured the hallux valgus angle (HVA), the intermetatarsal angle between the first and second metatarsals (M1M2) and the first and fifth metatarsals (M1M5) on anteroposterior radiographs, and calcaneal pitch (CP) on lateral radiographs. We calculated the average HVA, M1M2, M1M5 and CP of both feet in patients who didn't receive surgical treatment. Results: Steinbrocker stages 1, 2, 3 and 4 were identified 39, 48, 44 and 65 patients, respectively. Disease duration and activity increased, whereas HVAand CPtended to increase and decrease, respectively, with advancing Steinbrocker stages. However, M1M2 and M1M5 did not differ at any stages. These findings indicate that spreadfoot started from the early stage of RA. Conclusions: Foot deformities correlated with disease stage and duration in patients with RA, but spreadfoot started from an early stage. Foot problems are thought to develop within a 10-year period in almost all patients with RA, and inflammatory and mechanical factors leading to foot deformities must be medically addressed as soon as possible to avoid the progressive foot deformities that lead to disability. The relationship between foot deformities and disease stage in patients with RA should be evaluated in more detail. References: Bal A, Aydog E, Aydog ST, Cakci A. Foot deformities in rheumatoid arthritis and relevance of foot function index. Clin Rheumatol. 2006;25:671-675. Jhonson KA. Rheumatoid arthritis-forefoot. Surgery of the foot and ankle. Raven Pres, New York. 1989;245-264. Disclosure of Interest: K. Mamoto: None Declared, T. Koike Grant/Research support from: Takeda Pharmaceutical, Mitsubishi Tanabe Pharma Corporation, Chugai Pharmaceutical, Eisai, Abbott Japan, Teijin Pharma, Banyu Pharmaceutical and Ono Pharmaceutical, T. Okano: None Declared, M. Tada: None Declared, Y. Sugioka: None Declared, S. Wakitani: None Declared, H. Nakamura Grant/Research support from: Chugai Pharmaceutical, Astellas Pharma Inc., Janssen Pharmaceutica, GlaxoSmithKline, Pfizer Inc. and Daiichi Sankyo, INC., Speakers Bureau: Ono Pharmaceutical